Kajian Keberadaan Jenis-Jenis Penyakit-penyakit Tanaman Penting pada Cabai (Capsicum sp.) - Wali, Khalifa Listanti; Amanupunnyo, Handry R,D.; Tuhumury, Gratiana N.C (JURNAL PERTANIAN KEPULAUAN, 2025)
One of the causes of the decline in chili production in Indonesia is the disturbance of pests and diseases that attack at the time of seedling to harvest. The research aims to describe the damage caused by important diseases in chili plantations and obtain data on the intensity of damage caused by these diseases. This research used two varieties of chili, namely curly chili and cayenne pepper, and was conducted using the descriptive study method. The results of the study found 3 types of chili diseases, namely 1) leaf spot disease with an intensity of damage to curly chili of 19.58% and cayenne pepper of 11.57% in the mild attack category; 2) anthracnose disease with an intensity of damage to curly chili of 25.9% in the moderate attack category and cayenne pepper of 11.8% in the mild category; and 3) viral diseases with an intensity of damage to curly chili of 10% and cayenne pepper of 6% in the mild attack category.